Symbolic or Substantive? Women’s Political Participation and Its Impact on Legal Development in Afghanistan (2001–2021) - Aghamah Dehqanyar (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
This study rigorously analyzes women's political participation in Afghanistan throughout the Republican era (2001–2021), emphasizing whether this participation was largely symbolic or led to significant legal advancements. Subsequent to the collapse of the Taliban rule in 2001, Afghanistan implemented substantial legal and institutional reforms to advance gender equality, encompassing constitutional assurances and female quotas in the parliament. Notwithstanding these formal achievements, the degree to which women may affect legal and political outcomes remains disputed. This research employs feminist legal theory to examine the disparity between legal provisions and genuine political impact, utilizing qualitative content analysis of legal texts, policy frameworks, and electoral statistics. The data indicate that although women's political participation generated significant chances for representation and exposure, its overall effect was predominantly limited by structural, cultural, and political obstacles. The study suggests that women's involvement in Afghanistan was both symbolic and substantive; yet, symbolic representation frequently surpassed substantive influence, especially in critical decision-making processes. This underscores the inadequacies of formal legislative reforms in attaining authentic gender equality in post-conflict settings.